11种煎炸油煎炸薯条挥发性成分的组成Volatile compound composition of French fries prepared in 11 kinds of frying oils - 姚凌，徐立荣，蔡志鹏，季鑫，常佳睿，吴港城，王兴国YAO Ling, XU Lirong, CAI Zhipeng, JI Xin, CHANG Jiarui, WU Gangcheng, WANG Xingguo (Zhongguo youzhi, 2022)
利用顶空固相微萃取与气质联用相结合的方法测定了11种煎炸油煎炸薯条的挥发性物质组成，并对薯条进行感官评定。结果表明：11种煎炸油煎炸薯条共鉴定出包括醛类、含氧杂环类、含氮杂环类、酮类、醇类、酸类、烃类、含硫化合物和酯类化合物共80种挥发性物质，其中醛类化合物是煎炸薯条中主要的挥发性物质。 棕榈油煎炸薯条鉴定出的挥发性物质种类最多，亚麻籽油煎炸薯条的最少，且通过分析11种煎炸油煎炸薯条的醛类物质发现，葵花籽油和棉籽油煎炸薯条中多不饱和醛含量较高，其中(E，E)-2，4-癸二烯醛含量最高，是薯条呈现油脂香的主要物质；高油酸菜籽油和高油酸葵花籽油煎炸薯条中单不饱和醛含量较高，其中高油酸葵花籽油煎炸薯条中2-十一烯醛含量最高；亚麻籽油煎炸薯条中(E，E)-2，4-庚二烯醛含量最高，呈现出消费者不期望的脂肪味和油腻味。感官评定结果显示，棕榈油煎炸薯条品质最好，猪油煎炸薯条品质最差。 The volatile components of French fries prepared in 11 kinds of different frying oils were analyzed by headspace solid phase microextraction combined with GC-MS, and the sensory of French fries was evaluated. The results showed that a total of 80 compounds including aldehydes, oxygenated heterocycles, nitrogenated heterocycles, ketones, alcohols, acids, hydrocarbons, sulphur compounds and esters were identified in 11 types of French fries, with palm oil fries containing the greatest number of volatile substances and linseed oil fries the least, and aldehydes being the predominant volatile substance. Analysis of the aldehydes in 11 types of French fries revealed that French fries prepared in sunflower seed oil and cottonseed oil contained more polyunsaturated aldehydes, among which the conlent of (E, E)-2, 4-decadienal was the highest, which was the main substance that presented the oil fragrance. French fries prepared in high oleic acid rapeseed oil and high oleic acid sunflower seed oil contained more monounsaturated aldehydes, and French fries fried in high oleic acid sunflower seed oil had the highest content of 2-undecenal. French fries prepared in flaxseed oil contained the most (E, E)-2, 4-hepdienal, and it had a taste of fat and oil, which was disliked by consumers. Through sensory evaluation, the quality of French fries fried in palm oil was the best, while it was the worst fried in lard.